General health, dental status and perceived dental treatment needs of an elderly population in Istanbul - ÖZKAN, YASEMİN; ÖZKAN, YAŞAR (WILEY, 2011)
Background: Comprehensive data on the oral health status and dental treatment needs of the elderly population in Turkey are deficient. Objectives: This pilot study determined the general and dental health status, perceived medical and dental treatment needs of an elderly population dwelling in residential homes in Istanbul. Method: Subjects at three different residential homes, namely one belonging to the state and two supported by foundations in Istanbul (N=121, female: 63 and male: 58) were involved in this study. A detailed questionnaire was prepared and dental examinations were conducted. Information was collected related to age, education levels, financial status, current physical functional status, general health, mental health, previous dental history, current dental status, oral hygiene practices and denture hygiene of these elderly people. The prevalence of edentulism, the presence and type of dental prostheses, dental and denture status and denture cleanliness were further evaluated. Results: The three most prevalent reported general health problems were associated with genito-urinary problems (24%) followed by cardiovascular (18%) and respiratory problems (14%) varying significantly between genders, with males suffering more from cardiovascular problems than females (p < 0.05). Females showed significantly higher gastrointestinal and orthopaedic problems than males (p < 0.05). Females were more frequently edentulous than males but denture hygiene was significantly better in females than in males (p < 0.05). Brushing frequency did not significantly increase denture hygiene (p = 0.6). More than one-third of the subjects had not been to the dentist within the previous 5-10 years, mainly due to lack of demand, followed by the cost of the dental care and fear. More than two-thirds of denture-wearing subjects wore their dentures only during eating. Conclusions: There was significant perceived dental treatment and care need for the sample population of elderly studied.
Keywords: ageing; edentulousness; elderly people; oral and general health status; ORAL-HEALTH; PROSTHODONTIC TREATMENT; EDENTULISM; ADULTS; STOMATITIS; NUTRITION; SERVICES